Fearing the worst yet to come: Derrida and health anxiety. (August 2021) - Kelly, Molly
Building from the works of Jacques Derrida, this article explores health anxiety's aporetic relationship with medicine through a deconstructive approach. I argue that attention to Derrida's writings (and in particular, his readings of pharmakon and autoimmunity ) may prove useful in explaining the cyclical character of health anxiety and its ambivalent response to medical reassurance. What's more, I demonstrate how structuralist interpretations of health anxiety as a signifier without referent prove insufficient within a Derridean account. Such a reading emphasizes the need for interdisciplinary medical humanities as well as critical reflections on the possible limitations of Western medical semiotics.